Analysis of abiotic and biotic stress-induced Ca2+ transients in the crop species Solanum tuberosum - van Dieren, Annelotte; Schwarzenbacher, Roland E.; Sonnewald, Sophia; Bittner, Andras; Vothknecht, Ute C. (Scientific Reports, 2024)
Secondary messengers, such as calcium ions (Ca2+), are integral parts of a system that transduces environmental stimuli into appropriate cellular responses. Different abiotic and biotic stresses as well as developmental processes trigger temporal increases in cytosolic free Ca2+ levels by an influx from external and internal stores. Stimulus-specificity is obtained by a certain amplitude, duration, oscillation and localisation of the response. Most knowledge on stress-specific Ca2+ transient, called calcium signatures, has been gained in the model plant Arabidopsis thaliana, while reports about stress-related Ca2+ signalling in crop plants are comparatively scarce. In this study, we introduced the Ca2+ biosensor apoaequorin into potato (Solanum tuberosum, Lcv. Désirée). We observed dose-dependent calcium signatures in response to a series of stress stimuli, including H2O2, NaCl, mannitol and pathogen-associated molecular patterns (PAMPs) with stimuli-specific kinetics. Direct comparison with Arabidopsis revealed differences in the kinetics and amplitude of Ca2+ transients between both species, implying species-specific sensitivity for different stress conditions. The potato line generated in this work provides a useful tool for further investigations on stress-induced signalling pathways, which could contribute to the generation of novel, stress-tolerant potato varieties.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Aequorin; Arabidopsis thaliana; Calcium signalling; Crops; Potato; Stress perception